Analogia entre lógica e ética: a proposta husserliana de uma ética formal - Pereira, Fernanda da Silva Rodrigues (2013)
The present work is intended for examining the Husserlian propose of formal ethics in the light of the idea of the analogy between logic and ethics, limited to the pre-war lectures, focusing especially on the three Vorlesungen über Ethik und Wertlehre, courses taught by Husserl from 1908 to 1914, and occasionally on Logical Investigations and Ideas I. From the thesis of the parallelism among philosophical disciplines, the first chapter presents the most general elements that constitute the idea of analogy between logic and ethics, which play the role of analogue guiding principle in order to find parallel structures in the affectivity sphere. Afterwards, by means of the reconstruction of issues related to the intention of feelings and will contained in Vorlesungen, it is shown to what extent it is possible to maintain values as objects, which compound the thematic field of theoretical and formal ethics. Finally, the last chapter considers the subjects which constitute formal ethics. Originally it is about the exposition of formal axiology, which addresses the emotion sphere upon the exhibition of formal laws governing the valuations and, besides it, of a formal practice regarding the laws of will and wanting in the strict sense, culminating in the problem of the categorical imperative. Thus, the idea of analogy and logic is instructive and considerably limited at the same time.